Indigenous Perspectives on Sacred Natural Sites
1 online resource (246 pages)
Keywords: Much previous literature on sacred natural sites has been written from a non-indigenous perspective. In contrast, this book facilitates a greater self-expression of indigenous perspectives regarding treatment of the sacred and its protection and governance in the face of threats from various forms of natural resource exploitation and development. It provides indigenous custodians the opportunity to explain how they view and treat the sacred through a written account that is available to a global audience. It thus illuminates similarities and differences of both definitions, interpretations and governance approaches regarding sacred natural phenomena and their conservation. The volume presents an international range of case studies, from the recent controversy of pipeline construction at Standing Rock, a sacred site for the Sioux people spanning North and South Dakota, to others located in Australia, Canada, East Timor, Hawaii, India, Mexico, Myanmar, Nigeria and the Philippines. Each chapterincludes an analytical introduction and conclusion written by the editors to identify common themes, unique insights and key messages.The book is thereforea valuable teaching resource for students of indigenous studies, anthropology, religion, heritage, human rights and law, nature conservation and environmental protection. It will also be of great interest to professionals and NGOs concerned with nature and heritage conservation.